Medical Personnel’s Perceptions of the Implementation of Artificial Intelligence at Hospital Context - Nadila, Devita; Arianto, Radityo Fajar (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study examines how medical personnel perceptions influence the acceptance of artificial intelligence in hospital services in the Cilegon area. It advances technology adoption literature by demonstrating that AI acceptance in healthcare is driven less by cognitive evaluation and more by capability-building mechanisms, particularly training and digital literacy, which mediate perception–behavior relationships. Using a PLS-SEM approach with survey data from 159 health workers, the findings show that training and digital literacy exert the strongest influence on AI acceptance, while cognitive, affective, and conative perceptions do not directly translate into adoption. Instead, affective and conative dimensions operate indirectly through capability development pathways. These results underscore the centrality of experiential and participatory learning in shaping technology readiness among healthcare professionals. The study implies that hospital digital transformation strategies should prioritize structured training and digital literacy enhancement to ensure effective and sustainable AI integration.